1999
DOI: 10.5935/0305-7518.19990036
|View full text |Cite
|
Sign up to set email alerts
|

The stapedial reflex as a topographical marker of proximal involvement of the facial nerve in leprosy. A pilot study

Abstract: Summary This study aimed to determine the parameters necessary for a study of stapedial reflexes in leprosy patients to ascertain if the facial nerve is involved more proximally than the stylomastoid foramen. It involved leprosy patients with and without facial nerve involvement and non-leprosy controls. Clinical examination of the patients' ears, a tympanogram and audiogram to exclude conductive and sensorineural deafness, followed by the measurement of a stapedial reflex and the acoustic reflex threshold, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Os problemas auditivos, encontrados no indivíduo com hanseníase, são consequência do comprometimento do nervo vestibulococlear, levando a sintomas de vertigem, tontura e/ou náusea, à perda auditiva neurossensorial com presença de zumbido e dificuldade de compreensão de fala (10) . Já um estudo de 1999 não demonstrou alterações do reflexo estapediano devido à lepra (11) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os problemas auditivos, encontrados no indivíduo com hanseníase, são consequência do comprometimento do nervo vestibulococlear, levando a sintomas de vertigem, tontura e/ou náusea, à perda auditiva neurossensorial com presença de zumbido e dificuldade de compreensão de fala (10) . Já um estudo de 1999 não demonstrou alterações do reflexo estapediano devido à lepra (11) .…”
Section: Discussionunclassified
“…Lemieux L, Cherian TA, Richard B (11) Leprosy Review Journal The stapedial reflex as a topographical marker of proximal involvement of the facial nerve in leprosy. A pilot study…”
mentioning
confidence: 99%
“…[5][6][7][8] A higher incidence of cases has been reported in borderline tuberculoid (BT) leprosy of up to 40%, with an average time to onset of facial palsy ranging from 4 weeks to 12 years, the interval being lower when in type 1 reaction (T1R). 3,7,[9][10][11] In a study conducted among 1226 paucibacillary leprosy patients, lagophthalmos was present in 45% of patients with both a facial patch and T1R, 26% of patients with facial patch alone and in 8% of patients in T1R without facial patches. 12 Previous studies have shown that nerve conduction studies (NCS) may detect peripheral nerve dysfunction in leprosy earlier than the appearance of clinical signs and symptoms of nerve function impairment (NFI).…”
Section: Introductionmentioning
confidence: 99%